Development of novel diatom metrics to assess ecological status of phytobenthos in Greek lakes (2023)
Martyn Kelly Martyn, Steve Juggins, Kimon Moschandreou, Dimitra Kemitzoglou, and Vasiliki Tsiaoussi. 2023. Development of novel diatom metrics to assess ecological status of phytobenthos in Greek lakes. Ecological Indicators 147 (2023) 109974. https://doi.org/10.1016/j.ecolind.2023.109974.